MSME Economic Empowerment Through Community-Based Sharia Microfinance Program in DT Peduli Bogor - Pertiwi, Putri; Nawawi, M. Kholil; Triwoelandari, Retno (The Economic Review of Pesantren, 2024)
This study purpose to determine the Economic Empowerment of Micro, Small and Medium Enterprises (MSMEs) through the Program Microfinance Community-Based Sharia (Misykat) at Daarut Tauhid Peduli Bogor. This Economic Empowerment can be seen from the results of interviews with Misykat members. This study uses a phenomenological qualitative descriptive method. Data collection in this study used observation, interviews, and documentation with DT Peduli Bogor and Misykat members. The number of respondents in this study were 15 respondents. The data analysis method used is descriptive analysis. The result of this research is that DT Peduli Bogor carries out economic empowerment through the Misykat program to improve people's welfare. Forms of empowerment efforts carried out for members by providing revolving fund assistance in the form of capital loans and mentoring every week.